1, 25‐dihydroxyvitamin D deficiency accelerates alveolar bone loss independent of aging and extracellular calcium and phosphorus. Issue 8 (17th August 2018) - Gong, Aixiu; Chen, Jie; Wu, Jun; Li, Jing; Wang, Lin; Goltzman, David; Miao, Dengshun
Abstract: Background: Vitamin D is critical for bone homeostasis and immunomodulation. We therefore assessed whether 1, 25‐dihydroxyvitamin D (1, 25(OH)2 D) deficiency in mice with targeted deletion of the gene encoding 25‐hydroxyvitamin D‐1α‐hydroxylase (1α(OH)ase [1αOH)ase −/− mice]) results in alveolar bone loss and periodontal inflammation in vivo. Methods: Ten‐week‐old and 12‐month‐old 1α(OH)ase −/− mice and wild‐type littermates were fed a normal diet or a rescue diet, and the phenotype of the periodontium was then analyzed using microcomputed tomography, histology, immunohistochemistry, and real‐time Reverse transcription‐polymerase chain reaction (RT‐PCR). Results: Alveolar bone loss was increased and maxillary bone mineral density (BMD), osteoblast numbers, and the number of osterix‐positive cells were decreased significantly in 1α(OH)ase −/− mice compared with wild‐type mice. Although aging from 10 weeks to 12 months accentuated these changes, and a rescue diet reduced them, the alterations in the 1α(OH)ase −/− mice exceeded the effects of aging and diet change. Nuclear factor kappa light‐chain‐enhancer of activated B cells (NF‐кB) p65 and CD3 positive cells, and the gene expression levels of interleukin (IL)‐1β, tumor necrosis factor (TNF)‐α, matrix metalloproteinase (MMP)‐3 and ‐8 were all increased significantly in periodontal tissues of 1α(OH)ase −/− mice compared with wild‐type mice. Aging from 10 weeks to 12 months also accentuated these changes, and a rescue diet reduced them, however, the alterations in the 1α(OH)ase −/− mice exceeded the effects of aging and diet change. Conclusion: 1, 25(OH)2 D deficiency in the 1α(OH)ase −/− mice accelerated alveolar bone loss by inhibiting osteoblastic bone formation and enhancing periodontal tissue degeneration in a calcium‐ and phosphorus‐ as well as an age‐independent manner.